Identifikasi Cara Guru Mengajar Siswa Membaca, Menulis, Berhitung (Calistung) Pada Masa Pandemi di Kelas 1 SDN 213 Inpres Lemo - Yohanis Padallingan (LPPM UKI Toraja, 2022)
This research is a descriptive qualitative research located at SDN 213 Inpres Lemo, Sarira Village, North Makale District, Tana Toraja Regency. Sources of interview data were obtained through class I teachers, data collection techniques in this study were interviews, observation, and documentation. The data analysis used is data reduction, data presentation, and conclusion drawing, as well as testing the validity of the data by triangulation. The result of this research is the method or method used by the teacher in teaching students to read, write, and count. The purpose of this study was to find out the method used by class I teachers at DN 213 Inpres Lemo in teaching students to read, write and count.